STRATEGI REKRUTMEN PEGAWAI DI DINAS PUPR KABUPATEN SERANG - Ginanti Fajar (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This study aims to find out how the employee recruitment strategy at the PUPR service in Serang Regency in 2022. This study seeks to understand how the employee recruitment strategy at the PUPR service in Serang Regency in 2022. Therefore, the approach used in this study is a qualitative approach. The results of the research by researchers can be concluded: The recruitment process is not carried out directly by the PUPR Office of Serang Regency, but by submitting the required number of apparatus resources to the Regional Personnel Agency (BKD), then the BKD will send the number of employees needed by the PUPR Office Serang District obtained from the procurement or recruitment of personnel resources, both honorary staff or non-permanent employees (PTT) as well as apparatus resources obtained through the selection process for Civil Servant Candidates (CPNS) from general applicants